2014
DOI: 10.1364/oe.22.015992
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based optical filtering by the silica microshell of the centric marine diatom Coscinodiscus wailesii

Abstract: Diatoms are a renewable (biologically reproducible) source of three-dimensional (3-D) nanostructured silica that could be attractive for a variety of photonic devices, owing to the wide range of quasi-periodic patterns of nano-to-microscale pores available on the silica microshells (frustules) of various diatom species. We have investigated the optical behavior of the silica frustule of a centric marine diatom, Coscinodiscus wailesii, using a coherent broadband (400-1700 nm) supercontinuum laser focused to a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Since diatoms are so widespread and biologically successful although they are not motile, the frustule presumably has some other biological advantage [4][5][6]. Even though well investigated, the functionality of the frustule is not fully understood but it has been shown that the frustule provides the diatom with several properties; protection from mechanical and biotic stress, efficient nutrition uptake and light harvesting properties [4,[7][8][9][10][11][12]. In this work, focus is on how monochromatic light is transmitted through the valve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since diatoms are so widespread and biologically successful although they are not motile, the frustule presumably has some other biological advantage [4][5][6]. Even though well investigated, the functionality of the frustule is not fully understood but it has been shown that the frustule provides the diatom with several properties; protection from mechanical and biotic stress, efficient nutrition uptake and light harvesting properties [4,[7][8][9][10][11][12]. In this work, focus is on how monochromatic light is transmitted through the valve.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, light can be transmitted through the valve with diffraction from the foramen (holes) as the important effect. We are interested in developing a simple description of the multiple interference points described in simulations at a distance corresponding to outside the frustule when light interacts with the valve of the centric species Coscinodiscus granii (C. granii) [10,[12][13][14][15]. These interference points have been discussed on a theoretical basis and a few have been showed experimentally [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…diatoms, the exoskeleton surfaces include up to three layers of pore structures, with pore sizes ranging from 60 nm to 1 μm. These hierarchical, porous structures give rise to the diatom frustules' extraordinary mechanical strength 4 , enormous surface area 5 , and unique optical properties 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the ability to manipulate the frustules on a large scale, combined with simple arraying techniques 20 , may enable the development of practical, real-world applications using diatoms. However, despite the promise of the use of diatom frustules in a variety of areas, the unique properties of diatoms have typically only been studied on the scale of a single diatom frustule (requiring only individual diatom alignment) [6][7][8][10][11][12][13][14][15][16] or as bulk materials (requiring no significant alignment) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Setting diatoms apart from other phytoplankton is the nanostructured silica shell surrounding the protoplasm, called the frustule unique for each of the over 200000 different species [2,3]. Even though well investigated the functionality of the frustule is not fully understood but it has been shown that the frustule provides the diatom with several properties; protection from mechanical and biotic stress, efficient nutrition uptake and light harvesting properties [4,[5][6][7][8][9][10]. In this work the focus how linear polarized monochromatic light is transmitted through the valve in air.…”
Section: Introductionmentioning
confidence: 99%